Analysis Of Nicotine Levels In Tingwe (Linting Dewe) Cigarette Using Ultraviolet-Vision Spectrophotometry Method - Suharyanto, Suharyanto; Rahmadhani, Annisaa Shafaa (Pharmacon: Jurnal Farmasi Indonesia, 2023)
The most hazardous ingredient in cigarette tobacco is nicotine, which is also the main ingredient. In addition to being addicting, nicotine can cause cancer and lung issues. Tingwe cigarettes are produced locally with basic equipment and no addition of extra substances. The study's goal was to use UV Spectrophotometry to ascertain the amount of nicotine present in Tingwe cigarettes. According to the data, the nicotine content of brands A, B, and C was 1.5496 mg/cigarette (CV = 0.0382%, 2.1169 mg/cigarette (CV = 0.0096%), and 1.9987 mg/cigarette (CV = 0.0139%). Government Regulation Number 81 of 1999 states that a cigarette of tobacco can only contain 1.5 mg of nicotine, hence Tingwe brands A, B, and C do not adhere to this regulation.